Omics technologies used in pesticide residue detection and mitigation in crop - Goh, Meng Shien; Lam, Su Datt; Yang, YaFeng; Naqiuddin, Mohd; Addis, Siti Nor Khadijah; Yong, Wilson Thau Lym; Luang-In, Vijitra; Sonne, Christian; Ma, Nyuk Ling (Journal of hazardous materials, 2021)
In agriculture, the convenience and efficacy of chemical pesticides have become inevitable to manage cultivated crop production. Here, we review the worldwide use of pesticides based on their categories, mode of actions and toxicity. Excessive use of pesticides may lead to hazardous pesticide residues in crops, causing adverse effects on human health and the environment. A wide range of high-tech-analytical methods are available to analyse pesticide residues. However, they are mostly time-consuming and inconvenient for on-site detection, calling for the development of biosensors that detect cellular changes in crops. Such new detection methods that combine biological and physicochemical knowledge may overcome the shortage in current farming to develop sustainable systems that support environmental and human health. This review also comprehensively compiles domestic pesticide residues removal tips from vegetables and fruits. Synthetic pesticide alternatives such as biopesticide and nanopesticide are greener to the environment. However, its safety assessment for large-scale application needs careful evaluation. Lastly, we strongly call for reversions of pesticide application trends based on the changing climate, which is lacking in the current scenario. [Display omitted] •Discrepancy of pesticide usage and crop production.•Pesticide causes the loss of biodiversity and climate change.•Detection of biomarkers is the future trend in pesticide biosensor development.•Biopesticide and nanopesticide are new alternative of synthetic pesticide.